2009
DOI: 10.1002/cne.22060
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of calbindin‐D28k and calretinin in the brainstem of anuran and urodele amphibians

Abstract: Calbindin-D28k (CB) and calretinin (CR) are calcium binding proteins present in distinct sets of neurons; they act as buffers regulating the concentration of intracellular calcium. CB and CR immunohistochemistry was studied in the brainstem of anuran and urodele amphibians in combination with other markers (choline acetyltransferase, tyrosine hydroxylase, and nitric oxide synthase), which served to clarify the localization and signature of many cell groups. CR labeled the retinorecipient layers of the optic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
30
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 177 publications
11
30
0
Order By: Relevance
“…The evidence for this is the following: First, in other organisms in which these have been studied (mostly mammals), these markers specifically label neural structures [9], [10], [16]. Second, in the holothurian studied here, immunoreactivity to these markers is observed in cells and fibers of the radial nerve cords, podial nerves and peripheral nerves, which are the classically described neural structures in the echinoderms [27], [29], [30], [38]–[40].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The evidence for this is the following: First, in other organisms in which these have been studied (mostly mammals), these markers specifically label neural structures [9], [10], [16]. Second, in the holothurian studied here, immunoreactivity to these markers is observed in cells and fibers of the radial nerve cords, podial nerves and peripheral nerves, which are the classically described neural structures in the echinoderms [27], [29], [30], [38]–[40].…”
Section: Discussionmentioning
confidence: 76%
“…In vertebrates, specifically in mammals, calbindin 1, parvalbumin and calbindin 2 are present in different populations of neurons and interneurons of mice adult spinal cord [10]. In amphibians, differential immunoreactivity to anti-calbindin 1 and anti-calbindin 2 in cells and fibers throughout the brainstem serves to determine the localization and signature of many cell groups [9]. Lastly, calbindin 1 and calbindin 2-like immunoreactivities are present in the retina of the lamprey, the basal vertebrate studied at present [16].…”
Section: Introductionmentioning
confidence: 99%
“…The specificity of the antibodies used has been assessed by the commercial companies (Table 2) and, in addition, the immunoblotting conducted in our previous studies with Xenopus laevis showed that all antibodies used labeled a single band, which corresponded well (with minor variations) to the bands labeled in the rat lanes (see Morona and González, 2008, 2009; Morona et al, 2011; Moreno et al, 2012a; Domínguez et al, 2013a). …”
Section: Methodsmentioning
confidence: 99%
“…Their relative localization was framed attending to the neuromeric organization of the brain. We used the same nomenclature as in our previous studies (Morona and González, 2008, 2009, 2013; Domínguez et al, 2011, 2013a,b; Morona et al, 2011). Single and double-labeled sections were analyzed with an Olympus BX51 microscope equipped for fluorescence with appropriate filter combinations, and selected sections were photographed using a digital camera Olympus DP72.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation